2016
DOI: 10.1080/17451000.2016.1154576
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Yangtze River discharge on the genetic structure of a population of the rock bream,Oplegnathus fasciatus

Abstract: As a rocky reef species, Oplegnathus fasciatus displays significant geographic differences that may be congruent with patterns of molecular variation. We used 10 polymorphism microsatellite loci to characterize the genetic structure and test the impact of ocean currents and the Yangtze River on the population genetic connectivity of the rock bream, O. fasciatus, sampled from Jiaonan (JN), Zhoushan (ZS) and Taiwan (TW). The average number of alleles was 17.78, with a total of 160 alleles, and the average allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The Yangtze River estuary is known to be a notable barrier for the distribution of many marine invertebrates with lower gene flow, such as two oyster congeners of C. gigas and C. angulata (Xu, 1997;Li et al, 2017), an interpopulation of limpet (Cellana toreuma) (Dong et al, 2012) and the bivalve Cyclina sinensis (Ni et al, 2012(Ni et al, , 2017. Even marine species exhibiting high gene flow with high mobility or a long-term larval stage showed a distinctive genetic structure between the northern and southern coasts of the Yangtze River (Xu et al, 2009;Xiao et al, 2016). In addition, in line with a previous study (Xiao et al, 2010), oysters inhabiting the Yangtze River estuary were clustered with their northern counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Yangtze River estuary is known to be a notable barrier for the distribution of many marine invertebrates with lower gene flow, such as two oyster congeners of C. gigas and C. angulata (Xu, 1997;Li et al, 2017), an interpopulation of limpet (Cellana toreuma) (Dong et al, 2012) and the bivalve Cyclina sinensis (Ni et al, 2012(Ni et al, , 2017. Even marine species exhibiting high gene flow with high mobility or a long-term larval stage showed a distinctive genetic structure between the northern and southern coasts of the Yangtze River (Xu et al, 2009;Xiao et al, 2016). In addition, in line with a previous study (Xiao et al, 2010), oysters inhabiting the Yangtze River estuary were clustered with their northern counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the Yangtze (Chang Jiang) River has long been rendered as a marine biogeographic boundary causing distinct ecological gradients, especially for temperature and salinity, and shaping adaptive differentiations in warm-tolerant and coldwater populations or species of coastal animals under spatially varying selection. Ni et al (2017) comprehensively summarized the effects of the Yangtze River as well as its interaction with coastal currents on the genetic diversity of many marine species, such as fishes, crabs, mollusks, etc., Most of the marine species exhibited divergent genetic structures between the northern and southern populations separated by the Yangtze River, while coastal currents facilitate internal gene flows within the northern or southern populations (Xu et al, 2009;Xiao et al, 2016;. These findings highlight the significant role of stochastic geographic isolation following environmental selection in ecological, evolutionary, and taxonomic studies.…”
Section: Introductionmentioning
confidence: 88%
“…Combined with contributions from other rivers, a large delta plain with an area of more than 3 × 10 4 km 2 has developed (Saito, Yang, & Hori, ), and a sedimentary coast of mud substrate has been formed from Lianyungang (34°36′N, 119°13′E) to Shaoxing (30°19′N, 120°46′E) with a straight‐line distance of over 500 km (Zhu, Gao, & Zhu, ) (Figure a). These environmental changes may have drastically influenced phylogeographic patterns of coastal species (with low tolerance to salinity changes or with habitat specificity) and left genetic signatures in contemporary populations (Wang, Tsang, & Dong, ; Xiao, Ma, et al., ).…”
Section: The Yangtze River Outflow: History and Featuresmentioning
confidence: 99%
“…The standing genetic variation of a species is the outcome of its evolutionary history shaped by mutation, selection and genetic drifts ( 46 ). Past and on-going climate and geological events may leave signatures of selection or bottleneck in the genome and influence the geographic distribution of genetic variation ( 7–9 ). Many recent studies have revealed the significance of phenotypic plasticity in environmental adaptation ( 1015 ).…”
Section: Figmentioning
confidence: 99%